Microbiome Relationship in Autism Spectrum Disorder (ASD): Subject Review - Hiba Hazim Hamid; Kais Kassim Ghaima (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Importance of gut microbiota during neurodevelopment has increased, as has the potential relationship between the gut microbiota and (ASD). Complex associations between gut microbiota and ASD are explored here, including significant pathways such as immune modulation, neurotransmitter control, and gut-brain axis signaling. Based on available data, individuals with ASD possess distinctive microbial signatures that are characterized by reduced diversity and altered abundance of specific bacterial species. Such modifications could be related to symptoms of the behavioral nature, neuroinflammatory, as well as gastrointestinal. ASD growth as well as severity could be influenced by the composition of microbiome, depending on genetic, nutrition, microbial exposure during the earliest phases, as well as antibiotic use. Additional therapies based on the microbiome that presented the potential to alleviate the symptoms related to ASD include the use of probiotics, prebiotics, diet modification, as well as fecal microbiota transplantation (FMT). Still, establishing the causal associations, standardizing the procedure of handling the patients, as well as solving the problem related to the manipulation of microbiome, are still challenging activities, though. Large-scale, long-term studies need to be the core agenda of subsequent research, so that specific microbial signatures associated with ASD will be clearly defined, as well as tailored therapies that address the microbiome will be developed. Understanding more about the role that the microbiota plays during ASD may open up the diagnosis as well as the therapy based on the entirely new concepts, something that will ultimately benefit the patients who possess the disorder.